Analisis Hukum Hilangnya Hak Kepemilikan Tanah Masyarakat Pesisir Bintan Akibat Peraturan Agraria - Nuriani, Lia; Suryadi, Suryadi; Sudiarni, Sudiarni (Penerbit Goodwood, 2023)
Purpose: To explain the struggle in obtaining and utilizing natural resources, including land, the current legislation is unable to protect the rights of the community and tends to give more rights to the owners. Methods: This research is typical (normative). Primary legal materials, or primary legal materials that have authority, and secondary legal materials are two types of research sources Result: The government must also play a role in placing land along the coast because someone must regulate land to ensure the safety of people living along the coast. Agrarian regulations for coastal communities have legal certainty regarding the possibility of eliminating land rights if the land is given to the state and destroyed. The allocation, use, provision and maintenance of land are all regulated and managed by the state. Limitations: Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands, management of coastal areas and small islands must have HP-3 (Coastal Water Management Rights) (UU PWP-PPK). Contribution: Basic Agrarian Regulations, promulgated based on Law no. 5 of 1960, provides legal certainty regarding the elimination of ownership rights to land when it is handed over to the state and destroyed.